A new species of Dexoris (Coleoptera: Lycidae) and parallel evolution of brachyptery in the soft-bodied elateroid beetles - Bocak, Ladislav; Grebennikov, Vasily V.; Masek, Michal (Zootaxa, 2013)
Dexoris chome sp. nov. is described from South Pare mountains, Tanzania, based on a male specimen. This is the only Dexoris with shortened elytra, rudimentary hind wings and large, larviform abdomen. Unlike males of other species in the genus, D. chome sp. nov. has a modified number of palpomeres and remarkably short, robust legs and antennae. Such modifications are similar to those in the neotenic female of Omalisus fontisbellaquei Fourcroy, 1785 (Omalisidae), suggesting analogous morphological changes in unrelated lineages supposedly caused by similar modifications of their metamorphosis. The distribution of all 11 known species of African Dexoris closely overlap with the location of the hypothesized centres for evolution of new species in the Afrotropical region.